Hate crime in Turkey: implications of collective action, media representations and policy making - Göktan, Deniz Ünan (Cambridge Scholars Publishing, 2017)
"This book examines how hate crime, as a contemporary legal concept, is introduced and represented in Turkish public discourse. The study addresses questions of how effective the hate crime debate in Turkey has been in identifying bias-motivated violent incidents and how social institutions perceive hate crimes and influence the related debates instigated by social movement actors. First of all, the study explores the movement against hate crime in Turkey, and argues that hate crime has operated as an umbrella term, diverting distinct identity movements into dialogue and collaboration, but has also created a partial collective identity. Thereafter, to grasp the repercussions of the emerging anti-hate crime movement in the public discourse, the book focuses on the media and parliament. Accordingly, media and the governing bodies, in both direct and indirect ways, are shown here to constitute an impediment to the recognition of bias and prejudices." -- Back cover